2020
DOI: 10.3399/bjgp20x714101
|View full text |Cite
|
Sign up to set email alerts
|

Guidance impact on primary care prescribing rates of simple analgesia: an interrupted time series analysis in England

Abstract: Background: In March 2018, NHS England published guidance for Clinical Commissioning Groups (CCGs; NHS bodies that commission health services for local areas) to encourage implementation of policy to reduce primary care prescriptions of over-the-counter medications, including simple analgesia. Aims: To investigate: the impact of guidance publication on prescribing rates of simple analgesia (oral paracetamol, oral ibuprofen and topical non-steroidal anti-inflammatory drugs [NSAIDS]) in primary care; CCG impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Sasaki et al. ( 99 ) reported that deletion of interferon regulatory factor 4 (IRF4) can prevent kidney fibrosis after ischemic injury by decreased macrophage recruitment and activation in mouse model. Similarly, Chen et al.…”
Section: Macrophage Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Sasaki et al. ( 99 ) reported that deletion of interferon regulatory factor 4 (IRF4) can prevent kidney fibrosis after ischemic injury by decreased macrophage recruitment and activation in mouse model. Similarly, Chen et al.…”
Section: Macrophage Targeted Therapymentioning
confidence: 99%
“…Interferon regulatory factor 4 (IRF4) is a transcription factor from the IRF factor family that exerts regulatory functions in the immune system (98). Sasaki et al (99) reported that deletion of interferon regulatory factor 4 (IRF4) can prevent kidney fibrosis after ischemic injury by decreased macrophage recruitment and activation in mouse model. Similarly, Chen et al ( 100) confirmed that IRF4 deficiency can reduce kidney inflammation and fi brosis after acute kidney injury by suppressing macrophage infiltration.…”
Section: Macrophage Targeted Therapymentioning
confidence: 99%